Current tunable current-mode biquadratic filter using dual-output current followers - Bunruang, Kritsada; Prasertsom, Danucha; Pukkalanun, Tattaya; Tangsrirat, Worapong (My University, 2009)
This paper describes a current-mode multifunction filter with a minimum number of active and passive elements using dual-output current followers (DO-CFs) as active elements. By based on the dual-output current-controlled current conveyor (DO-CCCII)-based current followers, the proposed filter consists of only two DO-CFs and two grounded capacitor, without an external passive resistor requirement. The filter can realize all the standard biquadratic functions without changing the circuit configuration. Moreover, its natural angular frequency and bandwidth is controllable independently and electronically by adjusting an external bias current, and its active and passive sensitivities are low.